Effects of process parameters on the tensile properties of ABS/CB polymeric composites printed by fused filament fabrication - Tan, Kai Ni (Nanyang Technological University, 2022)
Fused filament fabrication (FFF) is an additive manufacturing (AM) technique that enables creation of relatively inexpensive parts that are available in different compositions. It has become one of the more widely used techniques due to its simplicity and the ability to create both multi-functional and multi-coloured parts. In this study, two different types of materials, namely acrylonitrile butadiene styrene (ABS) and carbon black ABS (ABS/CB) composites, will be investigated and compared in terms of their tensile strength correlating to process parameters. Additionally since FFF has the ability to print blended polymers, blended ABS with ABS/CB will be fabricated and tested as well. Fabrication of all the parts will be done using Geeetech A30M (FFF technique) and tensile testing will be performed with Shimadzu's 10kN tensile testing machine. To determine the most optimal parameter, ABS samples were tested first, then the following parameters were applied for ABS/CB samples. There were five variables tested namely extrusion multiplier, infill density, layer height, printing speed, and raster angle, all of which are listed in descending order of their effects on tensile strength. There was a significant difference observed between ABS/CB and ABS in terms of its material properties, resulting in a decreased tensile strength (35%) due to the carbon particles within. Moreover, the bonding between ABS/CB samples was evidently much weaker than that of ABS samples. When the same test parameters were applied, ABS/CB samples showed signs of delamination. As such, the extrusion multiplier parameter was increased in order to improve bonding, which was proven to be effective in increasing tensile strength. The tensile results of blended ABS with ABS/CB have shown similar performance to pure ABS/CB samples. Additionally, blended samples with a higher content of ABS/CB tended to have a lower tensile strength. From the results gotten, it has shown that blending of polymers allows user to vary the material composition without compromising significantly on tensile strength. This study therefore aims to provide a better understanding of how to obtain the ultimate tensile strength (UTS) of ABS, ABS/CB, and blended ABS with ABS/CB samples through optimising process parameters, which can then be useful for future studies.